The Constitutional Interpretation on the Natural Resource: Originalist Vs Non-Originalist Interpretation - Herdiansyah Hamzah (Hasanuddin Law Review, 2019)
Judges served in constitutional court have freedom to utilize and elaborate constitutional interpretation method used to examine the law of the Constitution of the Republic of Indonesia year 1945 in accordance to their own understanding. Not only that the constitutional interpretation was not regulated in positive law, judges also have independency in making new law discovery (rechtsvinding). Therefore, the interpretation method used by judges in the constitution court is basically determined by each case displayed at the moment. It means that the future of constitutional interpretation regulated by the judges in constitutional court is depending on the lawsuit reported in judicial review. On the other hand, constitutional interpretation on natural resource has to be based on original (originalist) interpretation rooted by original intent or text stated in the constitution of the republic of Indonesia year 1945, along with document of disagreement on its formulation (memorie van toelichting). Original interpretation is aimed at avoiding the shift at the origin of substantial intention of natural resources management.  Nevertheless, non originalis interpretation will remain usable, but it is limited only for technical level, so that natural resources management will stay updated while keeping the basic foundation of natural resources management as firmly stated in constitution.